Analisis dan Peningkatan Efektivitas Mesin Produksi Menggunakan Metode Overall Equipment Effectiveness (OEE) dan Failure Mode and Effects Analysis (FMEA) pada PT Alcotraindo Batam - Arif Disa Putra; Hery Irwan (Greenation International Journal of Engineering Science, 2026)
In the manufacturing industry, machine effectiveness plays a crucial role in achieving production targets, maintaining product quality, and improving operational efficiency. PT Alcotraindo Batam, as a manufacturing company, relies heavily on production machines to support its operational activities. However, machine downtime, performance losses, and equipment failures can reduce productivity and hinder the achievement of production objectives. Therefore, this study aims to analyze the effectiveness of production machines using the Overall Equipment Effectiveness (OEE) method and identify critical failure factors using Failure Mode and Effects Analysis (FMEA). This research employed a quantitative descriptive approach using production data, machine downtime records, maintenance reports, and quality data collected over a six-month observation period. The OEE analysis showed that the average machine effectiveness value was 76.40%, which is below the world-class standard of 85%. The average Availability Rate, Performance Rate, and Quality Rate were 88.32%, 88.00%, and 98.30%, respectively. Furthermore, the Six Big Losses analysis revealed that Equipment Failure Losses were the largest contributor to productivity losses, accounting for 35.14% of total losses. The FMEA results indicated that conveyor motor overheating was the most critical failure mode, with the highest Risk Priority Number (RPN) value of 320, followed by sensor malfunction (245) and roller wear (210). Based on these findings, several improvement strategies are recommended, including strengthening preventive maintenance programs, conducting routine inspections of critical components, enhancing operator training, and improving machine monitoring systems. The integration of OEE and FMEA proved effective in identifying machine performance losses and determining improvement priorities. The implementation of these recommendations is expected to increase machine effectiveness, reduce downtime, and improve overall production productivity at PT Alcotraindo Batam.